SOME ISSUES OF INTERDISCIPLINARY TEACHING OF MUSIC IN PRIMARY SCHOOL IN UZBEKISTAN - Ruziev D. Yu. (Academia Science Repository, 2023)
The article describes the features and methods of interdisciplinary teaching of music in the primary grades of secondary schools in Uzbekistan.